EFFECTS OF SOCIAL NETWORK ON STUDENTS’ PERFORMANCE: A WEB-BASED FORUM STUDY IN TAIWAN - Yang, Heng-Li (Online Learning, 2003)
This research investigates the effects of social networks on students’ performance in online education which uses networking as an adjunct mode for enhancing traditional face-to-face education or distance education. Using data from a 40-student course on Advanced Management Information Systems (AMIS), we empirically tested how social networks (friendly, advising, and adversarial) related to students’ performance. First, advising network variables are positively related to student performance both in the class and on the forum. Adversarial variables are negatively correlated with almost all students’ performance. Second, advising and adversarial network variables are good determinants for overall academic performance; however, adversarial network variables are not influential on students’ performance on the forum. Friendship network variables are not determinants of students’ performance. Implications for the results are also discussed.